Analisis Kelayakan Proses Evakuasi Vertikal pada Daerah Zona Merah di Kecamatan Kuta Alam - Isya, M.; Azmeri, Azmeri; Hasan, Enny Irmawati (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2021)
Kuta Alam Subdistrict is one of the Districts which are prone to tsunami disaster, 5 Gampongs from 11 Gampongs in Kuta Alam Sub-district are Gampong in the red zone, namely Gampong Lampulo, Gampong Lamdingin, gampong Lambaro Skep, Gampong Mulia, and gampong Peunayong. Based on the level of vulnerability, the five Gampongs are included in the Village which has a very high risk of tsunami. The main strategy to reduce disaster risk is to reduce casualties, namely by evacuating residents in vulnerable areas before the tsunami wave arrives in the area. Vertical evacuation is an evacuation carried out by moving residents from exposed areas by utilizing tall buildings or hills around vulnerable areas as evacuation sites. The feasibility of evacuation can be seen from the feasibility of the route, the feasibility of alternative evacuation buildings, travel time, and the mode used. From the analysis, it was found there is 11 alternative evacuation buildings can be used as evacuation buildings, where all buildings are declared feasible, and 11 evacuation routes, where only 1 route is declared feasible to be taken by vertical evacuation, while the other 10 routes are not feasible to walk